Application of Traditional Dakon Games in Improving Cognitive Abilities in Early Childhood - Annafi’ Nurul ‘Ilmi Azizah; Khusnul Wahyu Pradhana; Na’imatul Husna; Qorin Sauqi; Sifaul Sauqi; Mary Frances Hanline (Zuriah Jurnal Pendidikan Anak Usia Dini, 2024)
Abstract This research aims to understand how the application of the traditional dakon game can improve the cognitive abilities of young children through a qualitative approach using the interview and observation method. Dakon, or congklak, is a traditional game that has long been known in Indonesia and is believed to have significant educational value. This research involved in-depth interviews with teachers Bustanul Athfal Aisyiyah in Sukoharjo to collect data regarding their experiences and views on the impact of dakon games on children's cognitive development. Research results show that the dakon game helps children develop counting skills, strategic planning, memory and concentration. Additionally, this game is also reported to improve children's social and fine motor skills. Study participants noted that children who regularly played dakon showed significant progress in critical thinking and problem-solving skills. The conclusion of this research is that dakon games can be integrated into the early childhood education curriculum as an effective learning tool to support their cognitive development.